IMPs, VIMs and SPMs: the diversity of metallo-beta-lactamases produced by carbapenem-resistant Pseudomonas aeruginosa in a Brazilian hospital - Sader, Helio Silva [UNIFESP] (2005)
Pseudomonas aeruginosa isolates (n = 183), collected from bacteraemic patients hospitalised in São Paulo Hospital (Brazil) during 2000-2001, were screened for susceptibility to antimicrobial agents. the polymyxins were the most active compounds (100% susceptibility), followed by amikacin and cefepime (59.0%), meropenem (57.4%), and imipenem and gentamicin (55.2%). Imipenem-resistant isolates were ribotyped and screened for production of metallo-beta-lactamases (MBLs) by PCR with primers for bla(IMP), bla(VIM) and bla(SPM). MBL production was detected in 36 isolates (19.7% of the entire collection; 43.9% of the imipenem-resistant isolates) and the MBLs included SPM-1-like (55.6%), VIM-2-like (30.6%) and IMP-1-like (8.3%) enzymes.